Thematic Learning Tools Based on Collaborative Learning Models for Grade IV Elementary School - Ade Eka Anggraini; Mardhatillah; Oktaviani Adhi Subuatningsih; Oriza Zativalen; Khusnul Khotimah; Enio Kang Mohd Sufian Kang (International Journal of Elementary Education, 2024)
Collaborative learning model-based thematic learning tool is a tool that connects approaches between fields of study using the syntax of the collaborative learning model used to teach and learn in collaboration with group members to complete tasks, solve a problem or create a product. This development research aims to produce a thematic learning tool based on a collaborative learning model to improve the problem-solving ability of grade IV, which is tested for its validity level and feasibility. This development uses the Lee&Owens model. The results of the validity level test of the learning tools, including the syllabus, obtained a percentage result of 93.75%, with an excellent category. The Learning Implementation Plan and assessment instruments received a percentage result of 93.25% with a type are very valid; teaching materials obtained a percentage result of 88.63% to a kind were very valid, student worksheets (LKPD) got percentage results of 93.75% with a kind were very valid. The learning device e-book obtained a percentage result of 87.5%, which is very valid. The teaching material e-book got a percentage result of 94.19%, with a very valid type. The student response questionnaire sheet obtained a percentage result of 89%, which is very valid. The results of individual trials obtained a percentage of 91% with a type are a very valid and feasible category for use. The results of small group trials got a rate of 92.8%, with a very viable and valid variety for use. So, in general, validator assessment of learning devices provides conclusions that learning tools are worthy of implementation.